Optical and Electronic Properties of II-VI Group Semiconductor Nanomaterials from Energy Gaps - Jain, Rahul; M Singh, K (International Journal of Engineering and Technology, 2018)
A simple relation between the energy gap and refractive index is given for II-VI group semiconductors. Optical and electronic properties are evaluated by proposing a relation between energy gap and refractive index. The computed values are in fair agreement with the experimental values and earlier researches. This work emphasizes the understanding of interrelation between these parameters.Â Â